Suitability of phytoliths as a quantitative process tracer for soil erosion studies. Issue 9 (7th May 2021) - Kraushaar, Sabine; Konzett, Matthias; Kiep, Janika; Siebert, Christian; Meister, Julia
Abstract: Phytoliths are plant microfossils commonly used as qualitative archive markers in archaeological and paleoecological studies. Their potential uniqueness to the vegetation cover, robustness to weathering, and lack of chemical alteration along the transport paths make them potentially suitable tracers for quantitative erosion studies. In this pilot study, we explore the potential of phytoliths in a sediment fingerprinting study in the Ceguera catchment (28 km 2 ) in NE Spain. The phytolith concentrations and morphologies of four land cover classes (agricultural land, badland, forest, and shrubland) were analysed, and their contributions to four natural sediment mixture samples along the river course were modelled. Phytolith concentrations allowed us to discriminate sources sufficiently, albeit with limited sample size. The performance of the phytoliths as tracer was tested by reproducing the sources of artificial sediment mixture samples with satisfactory recall ratio. Results identified badlands to be the main contributor, with 84–96% of the sediment load to the sinks, followed by shrublands (median 5%) and agricultural lands (median 2%). These major findings can be reproduced by other conventional erosion studies from this area, indicating that phytoliths are suited to quantifying erosion patterns in mesoscale catchments. Abstract : In this sediment fingerprinting pilot study, the characteristics, composition, and concentrations of phytoliths proved to discriminate sediment sources in NE Spain sufficiently. Validation with artificial sink samples provided satisfying results for the small sample size of this pilot study. Fingerprinting results were compared to observed erosion processes and existing studies and yielded the same major contributors. Overall, we conclude that phytoliths seem a suitable tracer to quantify erosion patterns in mesoscale catchments, but need further testing with an extended sample.